Database-driven web sites - Morrison, Mike (Thomson/Course Technology, 2003)
Learn to build and deploy dynamic Web applications that interact with a powerful database. Readers with two prior programming courses will learn to get the most out of Visual Studio .NET, Oracle9i and Microsoft Access 2002